Morphology of contractile cardiomyocytes and vessels in pregnant rats and their pups exposed to hemic hypoxia - I. V. Zadnipryany; O. S. Tret'yakova; T. P. Sataieva; W. Zukow (Kazimierz Wielki University, 2015)
Zadnipryany I. V., Tret'yakova O. S., Sataieva T. P., Zukow W. Morphology of contractile cardiomyocytes and vessels in pregnant rats and their pups exposed to hemic hypoxia. Journal of Education, Health and Sport. 2015;5(4):72-80. ISSN 2391-8306. DOI: 10.5281/zenodo.16595 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%284%29%3A72-80 https://pbn.nauka.gov.pl/works/553142 http://dx.doi.org/10.5281/zenodo.16595 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02.2015. Accepted: 15.03.2015.   UDC 611.08: 611: 611.12 + 611.16   morphology of contractile cardiomyocytes and vessels IN PREGNANT rats AND their pups exposed to HEMIC HYPOXIA I. V. Zadnipryany, O. S. Tret'yakova, T. P. Sataieva, W. Zukow Medical Academy named after S.I. Georgievskiy Federal State Autonomous Educational Institution of Higher Education "Crimean Federal University" Kazimierz Wielki University, Bydgoszcz Summary          The  performed morphological  analysis of cardiomyocytes and myocardial vessels in 12 pregnant rats and 16 newborn pups exposed to the  hemic hypoxia induced by NaNO2  revealed  some  similar degenerative and destructive changes which were more pronounced in pups. The main morphological characteristics of hypoxic myocardial damage in pregnant and newborn rats were presented in the form of phenomena  of mixed dystrophy, swelling and destruction of endothelial cells and contractile cardiomyocytes along with the lysis of myofibrils, perivascular edema, capillary hyperemia, emptiness and spasm of the arterioles and contracture changes. Revealed pathological changes in the myocardium reflect the onset of myocardiodystrophy processes in pregnant rats and their newborn pups. Keywords: hemic hypoxia, cardiomyocytes, vessels, myocardium, pregnant rats, pups.